Algorithms and Complexity 8th International Conference, CIAC 2013, Barcelona, Spain, May 22-24, 2013. Proceedings - Spirakis, Paul G.; Serna, Maria; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed conference proceedings of the 8th International Conference on Algorithms and Complexity, CIAC 2013, held in Barcelona, Spain, during May 22-24, 2013. The 31 revised full papers presented were carefully reviewed and selected from 75 submissions. The papers present current research in all aspects of computational complexity and the use, design, analysis and experimentation of efficient algorithms and data structures.
Computational complexity and the use -- Design, analysis and experimentation -- Efficient algorithms -- Data structures.
Keywords: Computer science; Computer Communication Networks; Data structures (Computer science).; Computer software; Electronic data processing; Computational complexity; Computer graphics; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Data Structures; Numeric Computing; Computer Graphics; Computer Communication Networks